Presentation and management of snakebite envenomation in the uMkhanyakude district of KwaZulu-Natal (Mosvold Hospital) - Kabeya, Matamba Jean Benoit (Division of Emergency Medicine, 2025)
Background. Snakebites have been recognized as a neglected tropical disease by the World Health Organization (WHO) since 2009, and in 2017, was elevated to category A. South Africa (SA) has a well documented prevalence of snakebites, and there has been a recent surge in attention due to dwindling antivenom stocks. uMkhanyakude District in the far northeast of SA is known to use more antivenoms than elsewhere in SA, and thus seemingly to have the highest incidence of venomous snakebites in SA, yet no recent study has come from this district to describe snakebite management. Although there are various protocols and guidelines, as well as tools for assessing severity, none are standardized and it remains unclear what local management (and outcomes) are, particularly at the level of a small district hospital with arguably the highest incidence of snake bites in SA. Methods This study is a descriptive, retrospective observational study, describing all victims of snakebites presenting from 01st September 2019 to 31st August 2022 to a district hospital, Mosvold Hospital. Data was collected from patient's medical records. Information about demographics, clinical presentations, treatments and outcomes was collected and analysed. Results Some 155 snakebite cases presented, including 81 women (52.26%) and 74 men (47.74%). The incidence rate was 58 snakebite cases per 100000 people per years. Most patients were young, with a median age of 19 years (range 0-94 years), and most bites occurred outdoors (48.70%). Patients were most often bitten on the lower limb (69.03%), and most presented with minimal swelling - 117 patients (75.48%). Antivenom was administered to 33 patients (21.29%), and 24 (72.73%) of those who received antivenom experienced some form of post-antivenom reaction. Three patients died during their hospital stay, resulting in a mortality rate of 1.2 deaths per 100000 people per years.